Perancangan Sistem Cerdas Pemilihan Mobil Bekas Menggunakan Metode Fuzzy Mamdani - Karnadi, Very (Jurnal Sains Informatika Terapan, 2025)
Buying a used car is often an economical choice for people, but the selection process is not easy because it involves various subjective and uncertain criteria, such as engine condition, year of production, mileage, and price. To overcome these problems, this study designs an intelligent system that can help decision making in choosing a used car using the Mamdani fuzzy logic method. This system is designed to assess the suitability of a car based on input from several predetermined main variables, by utilizing fuzzy rules that are arranged based on expert knowledge. The results of this system are recommendations for the level of suitability of used cars, which can be used as a reference in the purchasing process. System testing shows that the Mamdani fuzzy method is able to provide fairly accurate and consistent results in evaluating and recommending used car choices that suit user needs. Thus, this system can be an effective and efficient tool in supporting the decision-making process for purchasing used cars.